Analisis Kohesi Leksikal dalam Novel Sesuk Karya Tere Liye - Daviria, Eqmi Avi; Hamidah, Jamiatul (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
The objective of this study is to describe and analyze the forms of lexical cohesion, specifically repetition, antonyms, synonyms, equivalence, collocations, and hyponyms, found in the novel Sesuk by Tere Liye. The research employs a qualitative method. The focus of the study is the markers of lexical cohesion in the novel Sesuk by Tere Liye. Data collection techniques used in this study are library research and note-taking. The findings indicate the presence of lexical cohesion forms, including 18 instances of repetition, 5 instances of antonyms, 2 instances of synonyms, 4 instances of equivalence, 2 instances of collocations, and 1 instance of hyponyms. In total, the lexical cohesion in the novel Sesuk by Tere Liye comprises 32 instances